2000
DOI: 10.1038/sj.bjp.0703357
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SB‐269970‐A, a selective 5‐HT7 receptor antagonist

Abstract: 1 The novel 5-HT 7 receptor antagonist, SB-269970-A, potently displaced [ 3 H]-5-CT from human 5-HT 7(a) (pK i 8.9+0.1) and 5-HT 7 receptors in guinea-pig cortex (pK i 8.3+0.2). 2 5-CT stimulated adenylyl cyclase activity in 5-HT 7(a) /HEK293 membranes (pEC 50 7.5+0.1) and SB-269970-A (0.03 ± 1 mM) inhibited the 5-CT concentration-response with no signi®cant alteration in the maximal response. The pA 2 (8.5+0.2) for SB-269970-A agreed well with the pK i determined from [ 3 H]-5-CT binding studies. 3 5-CT-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
209
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(226 citation statements)
references
References 34 publications
16
209
0
1
Order By: Relevance
“…For example, administration of the 5-HT 7 receptor-selective antagonists, SB-269970-A or DR-4004, to hamsters blocks phase advances of circadian locomotor activity rhythms induced by the serotonergic agonists, 8-OH-DPAT or 5-carboxamidotryptamine, demonstrating that pharmacological activation of 5-HT 7 receptors stimulates circadian phase resetting (Ehlen et al, 2001;Duncan et al, 2004). Also, administration of 5-HT 7 receptor-selective antagonists to guinea pigs or rats selectively decreases REM sleep, suggesting that endogenous serotonin acting at 5-HT 7 receptors exerts a tonic inhibition on REM sleep (Hagan et al, 2000;Thomas et al, 2003;Monti and Jantos, 2006). Furthermore, studies in mice have shown that deletion of the 5-HT 7 receptor gene impairs memory and learning (Roberts et al, 2004), reduces immobility in the Porsolt swim test, similar to antidepressants (Guscott et al, 2005;Hedlund et al, 2005), and inhibits hypothermia induced by 8-OH-DPAT (Hedlund et al, 2003).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, administration of the 5-HT 7 receptor-selective antagonists, SB-269970-A or DR-4004, to hamsters blocks phase advances of circadian locomotor activity rhythms induced by the serotonergic agonists, 8-OH-DPAT or 5-carboxamidotryptamine, demonstrating that pharmacological activation of 5-HT 7 receptors stimulates circadian phase resetting (Ehlen et al, 2001;Duncan et al, 2004). Also, administration of 5-HT 7 receptor-selective antagonists to guinea pigs or rats selectively decreases REM sleep, suggesting that endogenous serotonin acting at 5-HT 7 receptors exerts a tonic inhibition on REM sleep (Hagan et al, 2000;Thomas et al, 2003;Monti and Jantos, 2006). Furthermore, studies in mice have shown that deletion of the 5-HT 7 receptor gene impairs memory and learning (Roberts et al, 2004), reduces immobility in the Porsolt swim test, similar to antidepressants (Guscott et al, 2005;Hedlund et al, 2005), and inhibits hypothermia induced by 8-OH-DPAT (Hedlund et al, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…The 5-HT 7 receptor subtype, the most recently cloned of the serotonin receptor subtypes, modulates many physiological and behavioral functions, including circadian rhythms (Ehlen et al, 2001;Duncan et al, 2004;, rapid eye movement (REM) sleep (Hagan et al, 2000;Thomas et al, 2003;Monti and Jantos, 2006), body temperature (Hedlund et al, 2003), learning and memory (Roberts et al, 2004), and behavior (Guscott et al, 2005;Hedlund et al, 2005). For example, administration of the 5-HT 7 receptor-selective antagonists, SB-269970-A or DR-4004, to hamsters blocks phase advances of circadian locomotor activity rhythms induced by the serotonergic agonists, 8-OH-DPAT or 5-carboxamidotryptamine, demonstrating that pharmacological activation of 5-HT 7 receptors stimulates circadian phase resetting (Ehlen et al, 2001;Duncan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…WAY-100635 has selective 5-HT 1A receptor antagonist activity at the doses used in this study (Prinssen et al, 1999). The doses of SB-269970A were selected based on pharmacokinetic analysis (Hagan et al, 2000), doses of SB-243213A (5-methyl-1- [[2-[92-methyl-3-pyridyl0oxy]-5-pyridyl]carbamoyl]-6-trifluoromethylindone hydrochloride) were selected based on effects observed in a study by Wood et al, (2001).…”
Section: Drugsmentioning
confidence: 99%
“…31 It is still not conclusively known, however, whether and to what extent these actions contribute to therapeutic effects. Other potential roles for the 5-HT 7 receptor include regulation of circadian rhythms 28 and sleep, 32 thermoregulation, [33][34][35] learning and memory, 36,37 and endocrine regulation. 38,39 …”
Section: -Ht 7 : Therapeutic Possibilitiesmentioning
confidence: 99%